2021
DOI: 10.3389/fchem.2021.771473
|View full text |Cite
|
Sign up to set email alerts
|

Silylboronate-Mediated Defluorosilylation of Aryl Fluorides with or without Ni-Catalyst

Abstract: The defluorosilylation of aryl fluorides to access aryl silanes was achieved under transition-metal-free conditions via an inert C–F bond activation. The defluorosilylation, mediated by silylboronates and KOtBu, proceeded smoothly at room temperature to afford various aryl silanes in good yields. Although a comparative experiment indicated that Ni catalyst facilitated this transformation more efficiently, the transition-metal-free protocol is advantageous from a green chemistry perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In 2020, Shi et al also reported rhodium­(III)-catalyzed S N Ar alkoxylation using aryl fluorides and primary alcohols, proposing a Meisenheimer-type intermediate; however, most yields were moderate (43–77% and 97%; for an example, see Scheme b) . Recently, we reported the defluorosilylation of aryl fluorides via C–F bond cleavage, wherein a silyl boronate, Et 3 Si-BPin, facilitates the selective functionalization of the C–F bonds of aryl fluorides to generate C–Si bonds on aryl silanes (Scheme c) . Based on this transformation, we envisaged alkoxy variants of Et 3 Si-Bpin, that is alkoxyboronic acid pinacol esters (RO-Bpins), as effective reagents for introducing RO groups into fluoroaromatics via selective C–F bond cleavage.…”
mentioning
confidence: 99%
“…In 2020, Shi et al also reported rhodium­(III)-catalyzed S N Ar alkoxylation using aryl fluorides and primary alcohols, proposing a Meisenheimer-type intermediate; however, most yields were moderate (43–77% and 97%; for an example, see Scheme b) . Recently, we reported the defluorosilylation of aryl fluorides via C–F bond cleavage, wherein a silyl boronate, Et 3 Si-BPin, facilitates the selective functionalization of the C–F bonds of aryl fluorides to generate C–Si bonds on aryl silanes (Scheme c) . Based on this transformation, we envisaged alkoxy variants of Et 3 Si-Bpin, that is alkoxyboronic acid pinacol esters (RO-Bpins), as effective reagents for introducing RO groups into fluoroaromatics via selective C–F bond cleavage.…”
mentioning
confidence: 99%
“…In addition, the possible oxidative degradation mechanisms and pathways of BaP in the atmosphere have been explored by Dang et al (2015) . However, despite the involvement of transition metals in many catalytic processes ( Fujihara and Tsuji, 2019 ; Lin et al, 2021 ; Parmar et al, 2021 ; Sánchez-López et al, 2021 ; Yang et al, 2021 ; Zhou et al, 2021 ; Zhou et al, 2022 ), the use of transition metal complexes as non-sacrificial oxidants for the degradation of BaP has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, whereas it was almost exclusive toward the C2-silylation for quinolines having electron-neutral (alkyl or aryl groups, 2a – 2g ) or halide substituents ( 2h – 2j ), the selectivity was decreased with an electron-donating substituent ( 2k ). Noteworthy is that defluorosilylation, often encountered in the C–F bond activation by alkali bases, was not observed under our reaction conditions ( 2i – 2j ). Additionally, a biologically relevant quinoline derivative was viable to the desired selective silaboration ( 2l ).…”
mentioning
confidence: 99%